Object-oriented programming : - Cox, Brad J. (Addison-Wesley Pub. Co., 1991)
The first book published that fully describes object-oriented programming in an accessible manner for a wide range of readers. This new second edition covers the changes that have occurred in Objective C version 4.0, the newest release, and the tools that assist in developing object-oriented software.